Ventilation strategies for preventing oxidative stress-induced injury in preterm infants with respiratory disease: an update. (January 2016) - Aversa, Salvatore; Marseglia, Lucia; Manti, Sara; D'Angelo, Gabriella; Cuppari, Caterina; David, Antonio; Chirico, Gaetano; Gitto, Eloisa
Summary: Reactive oxygen and nitrogen species are produced by several inflammatory and structural cells of the airways. The lungs of preterm newborns are susceptible to oxidative injury induced by both reactive oxygen and nitrogen species. Increased oxidative stress and imbalance in antioxidant enzymes may play a role in the pathogenesis of inflammatory pulmonary diseases. Preterm infants are frequently exposed to high oxygen concentrations, infections or inflammation; they have reduced antioxidant defense and high free iron levels which enhance toxic radical generation. Multiple ventilation strategies have been studied to reduce injury and improve outcomes in preterm infants. Using lung protective strategies, there is the need to reach a compromise between satisfaction of gas exchange and potential toxicities related to over-distension, derecruitment of lung units and high oxygen concentrations. In this review, the authors summarize scientific evidence concerning oxidative stress as it relates to resuscitation in the delivery room and to the strategies of ventilation.